2002
DOI: 10.1172/jci0213870
|View full text |Cite
|
Sign up to set email alerts
|

Effects of reduced mucus oxygen concentration in airway Pseudomonas infections of cystic fibrosis patients

Abstract: Current theories of CF pathogenesis predict different predisposing "local environmental" conditions and sites of bacterial infection within CF airways. Here we show that, in CF patients with established lung disease, Psuedomonas aeruginosa was located within hypoxic mucopurulent masses in airway lumens. In vitro studies revealed that CF-specific increases in epithelial O 2 consumption, linked to increased airway surface liquid (ASL) volume absorption and mucus stasis, generated steep hypoxic gradients within t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
557
0
5

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 919 publications
(583 citation statements)
references
References 37 publications
(47 reference statements)
21
557
0
5
Order By: Relevance
“…Although many of these isolates can still behave as siderophore cheaters, exploiting the supply of pyoverdine provided by cooperative producers in mixed P. aeruginosa populations (70), recent evidence strongly suggests that other iron acquisition strategies can be employed by P. aeruginosa to persist in the chronically infected CF lung. Notably, it has been found that the soluble Fe 2ϩ ion represents the main iron source in late-stage CF disease (71), when oxygen tension in the lung is very low and P. aeruginosa grows mainly as dense, biofilm-like microcolonies in locally anoxic microenvironments (72). Conversely, the master regulator of the pyoverdine system, PvdS, was previously shown to be required for infection of tissues preferentially exposed to high O 2 tensions (30).…”
Section: Discussionmentioning
confidence: 99%
“…Although many of these isolates can still behave as siderophore cheaters, exploiting the supply of pyoverdine provided by cooperative producers in mixed P. aeruginosa populations (70), recent evidence strongly suggests that other iron acquisition strategies can be employed by P. aeruginosa to persist in the chronically infected CF lung. Notably, it has been found that the soluble Fe 2ϩ ion represents the main iron source in late-stage CF disease (71), when oxygen tension in the lung is very low and P. aeruginosa grows mainly as dense, biofilm-like microcolonies in locally anoxic microenvironments (72). Conversely, the master regulator of the pyoverdine system, PvdS, was previously shown to be required for infection of tissues preferentially exposed to high O 2 tensions (30).…”
Section: Discussionmentioning
confidence: 99%
“…While the oxygen concentration in the exposure medium did not alter the bactericidal efficacy of NO, the presence of oxygen during bacterial growth did influence P. aeruginosa susceptibility to NO. Anaerobic growth conditions reduce the efficacy of current antibiotics by altering certain properties of the bacteria, such as alginate production (46) and metabolic rates (10). To separate these factors, MBC 4 h assays were performed under nonnutritive conditions to minimize the effects of bacterial metabolism on the bactericidal activity of NO.…”
Section: Discussionmentioning
confidence: 99%
“…As bacterial biofilms exist in both aerobic and anaerobic environments (46), it was important to determine how oxygen concentrations affected the antibiofilm activity of COS-NO. Under aerobic conditions, highly viscous microcolony biofilms were formed (ϳ250 l in volume) with bacterial viability of 4.0 Ϯ 0.6 ϫ 10 8 and 2.5 Ϯ 0.5 ϫ 10 8 CFU/ml for nonmucoid and mucoid phenotypes, respectively.…”
Section: Inhibition Of Growth By Cos-no For Clinical Isolates Includmentioning
confidence: 99%
“…Such persistence is even more pronounced for P. aeruginosa, which in many patients persists lifelong once chronic airway infection has been established (76). Thus, CF airways provide a unique niche where bacteria face a hostile environment, with neutrophil influx (77), hypoxia (78), competition with coinfecting species (79), and antibiotic selective pressure (80), which lead to various forms of bacterial adaptation, including the emergence of SCVs (30).…”
Section: Cystic Fibrosis Airway Infectionmentioning
confidence: 99%